Dilla Jaidi's Personal Branding As A Beauty Content Creator Through Tiktok Social Media (An Analysis Of Tiktok Account @Dillajaidi) - Hati, Indah Prasepta; Putra, Dilmai; Maryaningsih, Maryaningsih (Universitas Dehasen Bengkulu, 2025)
The development of increasingly sophisticated communication technology has given birth to social media. One of the social media applications that is currently trending in Indonesia is TikTok. The presence of TikTok social media is used for individual activities to compete in terms of introducing or the public knows it as personal branding. One of the content creators who has utilized the presence of TikTok social media for personal branding activities is Dilla Jaidi. Dilla Jaidi is known as a beauty content creator on TikTok who specializes in make-up and skincare. This study aims to describe the personal branding carried out by Dilla Jaidi through TikTok social media @dillajaidi.This study uses a qualitative descriptive content analysis approach. The analysis was carried out using Peter Montoya's personal branding aspects. The data collection techniques used were observation and documentation. And the data analysis techniques used were data collection, data presentation, and drawing conclusions. The results of the study showed that Dilla Jaidi's personal branding form through TikTok social media @dillajaidi, she prioritized how she was seen as a beauty content creator. In accordance with the eight concepts of personal branding theory by Peter Montoya, TikTok social media @dillajaidi shows Dilla Jaidi as an expert as a beauty content creator, often also providing solutions according to the audience's needs. Dilla Jaidi displays a cheerful, warm figure and also a multi-talented beauty mentor. Beauty content as Dilla Jaidi's characteristic is not possessed by other beauty content creators. Dilla Jaidi consistently uploads content on make-up and skincare tips and tricks. The content shared by Dilla Jaidi on her TikTok social media is relevant to her daily life. The TikTok account @dillajaidi in producing content always has a positive influence on the audience.